Propuesta de mejora continua para el proceso de envasado en la boquilla de la maquina ensacadora, siendo un equipo eficiente, productivo y amigable con el medio ambiente y los trabajadores del área de plata de yeso en la empresa etex cartagena - Nestor Alexander, Viafara Perez; Alvaro José, Cueto Valdelamar (Universidad Antonio Nariño, 2023)
The main objective of this project is to analyze and find a strategy for the fault control of the bagging machine, based on the pertinent study and the theoretical investigation, it will proceed in the design of tools for the solution of industrial problems in order to determine what the genesis of the breakdown is, taking into account that the bagging machine is used to pack and package products such as: putty 90, rosemary, and projected in 25kg bags, made of recyclable material, this in order to contribute to quality, safety and environment. Identifying the cause of the nozzle failure is crucial to solving it. If the nozzle is the wrong size, it can be replaced with a suitable nozzle. Regular cleaning of the nozzle is also important to keep it working properly. In some cases, the failure may be related to the quality of the product, which can clog the nozzle. Clogging can be avoided by implementing quality controls and adapting the nozzle size